Opening Sequences in Technologically Mediated Conversation: A Comparative Study of Mobile and Landline Calls among Saudi Speakers - Alghammas, Abdurrazzag (Forum for Linguistic Studies, 2025)
This study investigates how mobile and landline communication influence the structure of conversational openings among Saudi Arabic speakers, employing Conversation Analysis (CA) as the guiding theoretical framework. Drawing on naturalistic recordings of informal conversations, the analysis engages with canonical CA models while accounting for technological affordances and cultural norms. The findings reveal systematic differences in mobile openings: caller identification is frequently omitted due to caller ID, greeting sequences are compressed or bypassed, and locational inquiries (e.g., “Where are you?”) increasingly serve as pragmatic substitutes for greetings. Topic initiation tends to occur earlier in mobile calls, often within the initial turn. While the principle of caller hegemony remains evident, instances of callee-led negotiation suggest greater interactional fluidity. Moreover, mobile calls exhibit quicker response times and a more accelerated conversational rhythm than landline calls. These results underscore the need to revise classical CA frameworks to accommodate mobile-specific practices, highlight location talk as an emergent structuring device, and illustrate how technological and cultural factors co-construct conversational norms in contemporary Saudi contexts. The study suggests that scholars stay alert to the ways in which local culture and emerging technologies are transforming the subtle dynamics of human interaction as mobile communication becomes increasingly integrated into daily life in Saudi Arabia and around the world. This study contributes to a more nuanced, context-sensitive understanding of mediated communication in an evolving technological landscape.